Introduction to the Symposium - Decarcerating Disability, Criminal Justice and Law: New Writing on Disability, Abolition and the Limits of Rights - Ben-Moshe, Liat; Steele, Linda (feminists@law, 2023)
Liat Ben-Moshe and Linda Steele introduce a Symposium on their 2020 publications Decarcerating Disability: Deinstitutionalization and Prison Abolition (Ben-Moshe) and Disability, Criminal Justice and Law: Reconsidering Court Diversion (Steele). Ben-Moshe and Steele introduce their own books and then identify connections between the books. They situate their discussion in the anti-carceral activism that emerged during 2020 and in longer term activist and scholarly work on deinstitutionalisation, prison abolition and rights in the criminal justice system.